Anti-aging Interventions: Caloric Restriction and Beyond - Khing S. Ong; Zack ST. Lim; Boenjamin Setiawan (PT Kalbe Farma Tbk., 2018)
Aging is the biggest risk factor for most of the age-related chronic diseases, which carried a heavy health-care costs burden worldwide. These age-related diseases, such as cardiovascular diseases, neurodegenerative diseases, cancers, type 2 diabetes, and osteoarthritis, shared common mechanisms that associate with aging, such as chronic sterile low grade inflammation, cellular senescence, DNA damages, and stem cells dysfunctions. In this review, we will first discussed the dietary manipulation, such as caloric restriction as the mean of delaying aging, and we will also review nutraceuticals or natural compounds, and pharmaceutical drugs as the mean for intervention of aging. Proses menua dikaitkan dengan berbagai penyakit kronis terkait-usia, yang mengakibatkan beban biaya perawatan kesehatan yang besar di seluruh dunia. Penyakit-penyakit tersebut meliputi penyakit kardiovaskuler, penyakit neurodegeneratif, kanker, diabetes tipe 2, dan osteoartritis, yang mempunyai gambaran umum serupa yaitu inflamasi steril kronis kadar rendah, penuaan sel, kerusakan DNA, dan disfungsi sel punca. Tinjauan ini berkenaan dengan manipulasi diet berupa restriksi kalori, dan nutraceuticals serta senyawa alami, juga sediaan farmakologis untuk tujuan mengintervensi proses penuaan